1992
DOI: 10.1111/j.2042-7158.1992.tb03633.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Mucoadhesive Polymer Polycarbophil on the Intestinal Absorption of a Peptide Drug in the Rat

Abstract: The absorption across rat intestinal tissue of the model peptide drug 9-desglycinamide, 8-arginine vasopressin from bioadhesive formulations was studied in-vitro, in a chronically isolated internal loop in-situ and after intraduodenal administration in-vivo. A controlled-release bioadhesive drug delivery system was tested, consisting of microspheres of poly(2-hydroxyethyl methacrylate) with a mucoadhesive Polycarbophil-coating, as well as fast-release formulation consisting of an aqueous solution of the peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(24 citation statements)
references
References 6 publications
0
22
0
2
Order By: Relevance
“…Table 3 also shows the potential of the mussel foot glue protein (Schnurrer and Lehr, 1996). Lehr et al (1992a) and Schnurrer and Lehr (1996) also obtained the rather surprising result of a very favourable interaction for the synthetic polyanionic polymer, polycarbophil. We will consider these results again later when we have dealt with the molecular hydrodynamics.…”
Section: Direct Assay Methods For Mucoadhesionmentioning
confidence: 99%
“…Table 3 also shows the potential of the mussel foot glue protein (Schnurrer and Lehr, 1996). Lehr et al (1992a) and Schnurrer and Lehr (1996) also obtained the rather surprising result of a very favourable interaction for the synthetic polyanionic polymer, polycarbophil. We will consider these results again later when we have dealt with the molecular hydrodynamics.…”
Section: Direct Assay Methods For Mucoadhesionmentioning
confidence: 99%
“…Longer and colleagues (Longer et al 1985) first showed that delayed GI transit induced by bioadhesive polymers could lead to increased oral bioavailability of a drug. Other researchers have prepared a multiunit bioadhesive system by coating microspheres of poly-hydroxyethyl-methacrylate with mucoadhesive polymers using laboratory-scale equipment (Lehr et al 1990(Lehr et al , 1992. Akiyama and coworkers (Akiyama et al 1995) prepared a polyglycerol ester of fatty acid-based microspheres coated with Carbopol934P (CP) and CP-dispersing microspheres to evaluate their mucoadhesive properties.…”
Section: Mucoadhesive Dosage Formsmentioning
confidence: 99%
“…Mucoadhesive polymers are available for localization or slow transit of microparticles at the gastrointestinal tract. 7,[9][10][11][12][13][14] In this study, ethylcellulose was used to prepare microparticles showing prolonged release of cephradine, and chitosan was applied to give the microparticles mucoadhesive characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…1,[6][7][8] Further, their gastrointestinal transit can be modified with mucoadhesive polymers. [9][10][11] When the mucoadhesive polymers interact with mucous membranes of the GI tract, they are considered to be localized or trapped at the adhesive sites, which may result in prolonged duration of absorption. 7,[12][13][14] Chitosan is adhesive to the intestinal mucosa, and chitosan enhances drug absorption from microparticulate dosage forms.…”
mentioning
confidence: 99%